Impact of dining out frequency on the risk of colorectal cancer: insights from a large Chinese cohort - Zhang, Pei; Xing, Wen-Jing; Zhang, Jing; Sun, Yin-Di (Frontiers in Oncology, 2025)
IntroductionDining out has been shown to be associated with various negative health outcomes. However, the evidence concerning the relationship between dining out of home and the risk of colon and rectal cancers remains limited.MethodsWe included a total of 42,286 participants aged between 20 and 60 years in this study, who underwent physical examinations at five large public hospitals located in Zibo, Shandong Province, China, from 2010 to 2022. Cox regression models were utilized to evaluate the association between the frequency of dining out and the risk of colon and rectal cancers, employing hazard ratios (HR) along with their corresponding 95% confidence intervals (CI). Restricted cubic spline (RCS) functions were applied to estimate the dose-response relationship. Subgroup analyses and sensitivity analyses were conducted to assess the robustness of the Cox regression models.ResultsDuring a median follow-up of 10.3 years, this cohort study identified 272 new cases of colon cancer and 181 new cases of rectal cancer. After adjusting for confounding factors, frequent dining out was linked to an increased risk of both cancers, with HR of 2.231 (95% CI = 1.656-3.007) for colon cancer and 1.793 (95% CI=1.231-2.611) for rectal cancer compared to those who dined out rarely or never. The non-linear dose-response relationship between the frequency of dining out and the incidence of colon and rectal cancers demonstrated a significant pattern. Furthermore, obesity significantly mediated the associations between dining out frequency and the risks of developing both cancers.DiscussionDining out frequently was significantly linked to an increased risk of colon and rectal cancer. Notably, obesity may partially mediate this relationship.